Institutions and Legitimations in Finance for the Arts - Ida Lunde Jørgensen (Copenhagen Business School (CBS), 2016)
The thesis contributes to a more nuanced understanding of art support by investigating the underlying legitimations and institutional logics of two of the most significant foundations supporting visual art, in Denmark, the private New Carlsberg Foundation and public Danish Arts Foundation. Drawing on insights from neo-institutional and French convention theory, the thesis makes its central contributions within the fields of neo-institutional theory, cultural policy and philanthropy studies. The first paper shows the suitability of neo-institutional theory, particularly the theories of isomorphism, cultural and institutional entrepreneurship, institutional logics, and rhetorical work to address a number of key debates in cultural policy pertaining to the evaluation of aesthetic performance, the justification of investment in the arts and how ideas and meanings become taken for granted in the cultural policy field. In addition, the first paper theorizes the wider field of cultural policy, suggesting twelve institutional arenas where cultural policy is unfolded, of which the thesis focuses on public and private foundations. In the second paper, the thesis focuses on uncovering the key legitimations of art support in the New Carlsberg Foundation and the Danish Arts Foundation at critical points in time, drawing on and contributing to the literature on institutional logics and convention theory. Specifically, the thesis shows the importance of nine particular logics of legitimation underlying art support; the industrial, market, inspired, family, renown, civic, projective, emotional and temporal. Most central to the foundations' operation are the professional (industrial), artistic (inspired) and civic logics. The thesis shows that the invocations of these logics are highly reflective upon wider societal institutions, prevailing institutional logics, the nature of the critical moment and the organisations' practices and purpose. In the third paper the thesis hones in on the temporal logic, and draws attention to the micro-level use of this logic, which suggests that logics are invoked in characteristic ways. The third paper illuminates five distinctive uses of the past in the New Carlsberg Foundation, pertaining to the charter, the founding family, place, the moment and anecdotes and importantly shows that while some of these uses are reflected and instrumental, others are institutionalised and show propensity towards institutional reification.
hdl:10398/9337
Keywords: 650